Persepsi Karyawan atas Implementasi Kepemimpinan Manajer di PT Dakar Eshan Abadi Tangerang Selatan - Mukrodi Mukrodi (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Leadership plays an important role in determining organizational effectiveness and employee performance in a company. This study aims to analyze the implementation of managerial leadership from the employees’ perspective at PT Dakar Eshan Abadi. The research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. Informants were selected using purposive sampling techniques and consisted of company managers and division heads who were directly involved in organizational leadership practices. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion verification. Data validity was ensured through source, technique, and time triangulation. The findings reveal that managers demonstrate effective communication skills, conflict management abilities, and the capacity to inspire employees. In managerial aspects, managers are actively involved in team development, strategic planning, employee motivation, and human resource management. From an entrepreneurial perspective, managers show opportunity-oriented behavior, creativity, and innovation in acquiring clients. Supervisory functions are implemented through monitoring and controlling sales activities, while socially, managers emphasize employee welfare and the development of an inclusive work culture. The study concludes that charismatic, democratic, and transformational leadership styles are predominantly applied within the company.